Anatomical relationship between the internal jugular vein and the vertebral artery: An observational study in pre-school children using ultrasound imaging - Anand Ganesh; Joseph P Paarel; Geethu E Punnen; Ragul Siddarth; Kunder S Prakash; Raj Sahajanandan (Wolters Kluwer Medknow Publications, 2022)
Background and Aims: Central venous cannulation is performed in children requiring vasopressor use, long-term antibiotics, chemotherapy or parenteral nutrition. The internal jugular vein is the preferred site for cannulation. Though, there are several studies describing the relation of the common carotid artery (CCA) and internal jugular vein (IJV) in the neck, there is a paucity of data regarding the anatomical relationship between the vertebral artery (VA) and the IJV. This study aims to describe the anatomical relationship between the IJV and the VA using ultrasound imaging in pre-school children in India. Material and Methods: Prospective observational cross-sectional study of 67 randomly selected children (age <5 years) who underwent an ultrasound examination of the right side of the neck, in a position mimicking central venous cannulation, to identify the relationship between the IJV and VA. The skin to the vertebral artery depth (D), width of the VA (W), distance between the IJV and the VA (DIV) was measured. Based on these, children were classified into high risk, moderate risk and low risk category for VA puncture. Results: Of the 67 children, 15 (22.4%) patients belonged to the high-risk group, 25 (37.3%) belonged to the moderate-risk group and 27 (40.23%) belonged to the low-risk group. Conclusion: In addition to localizing the carotid artery, pre-procedural scanning or real-time ultrasound examination to establish the anatomical relation of the IJV to the VA is imperative to alert the clinician of the possible risk of VA puncture.